Cover Image: Plasmodium berghei sporozoites in nonreplicative vacuole are eliminated by a PI3P‐mediated autophagy‐independent pathway (Cellular Microbiology 1/2021). (7th December 2020) - Bindschedler, Annina; Wacker, Rahel; Egli, Jessica; Eickel, Nina; Schmuckli‐Maurer, Jacqueline; Franke‐Fayard, Blandine M.; Janse, Chris J.; Heussler, Volker T.
Abstract: Immunofluorescence image of Plasmodium berghei sporozoites (red) in HeLa cells 1.5 hours post infection. The parasitophorous vacuole membrane (PVM) that surrounds the parasites was stained with antibodies against the PVM‐resident protein UIS4 (grey). DNA was stained with DAPI (blue). Imaging was performed on a Leica SP8 confocal microscope. For further details, readers are referred to the article by Bindschedler et al . on p. e13271 of this issue. Abstract : Immunofluorescence image of Plasmodium berghei sporozoites (red) in HeLa cells 1.5 hours post infection. The parasitophorous vacuole membrane (PVM) that surrounds the parasites was stained with antibodies against the PVM‐resident protein UIS4 (grey). DNA was stained with DAPI (blue). Imaging was performed on a Leica SP8 confocal microscope. For further details, readers are referred to the article by Bindschedler et al . on p. e13271 of this issue.